Increasing quality of life during the Covid-19 pandemic with the implementation of a clean and healthy life pattern - Asri Noviyanti (Community Empowerment, 2022)
The Covid-19 pandemic is now causing a global health problem. The purpose of this community service is to improve people's attitudes and understanding on the promotion of hygienic and healthy living practices. The program is carried out through lectures, brainstorming sessions, and questions and answers. People's attitudes and knowledge about living a clean and healthy lifestyle are improved as a result, making it easier for people to incorporate these practices into their daily lives. It is envisaged that this may lessen the spread of Covid-19 and enhance community well-being.